Design of a Mini Thermal Storage System for Air- Conditioning Service - Nik Mohamed Daud, Nik Mohd Radi (Universiti Teknologi Petronas, 2011)
Thermal energy storage is a system that distributes chilled water or other media to multiple buildings for air conditioning or other uses. Thermal Storage System systems are useful for maximizing the thermal energy efficiency for meeting the fluctuating cooling demands by shifting energy use from on peak to off-peak hours by charging the Thermal Storage Tank during the off-peak hours and discharging it later during the peak hour. For this reason, they are now receiving much attention among the world. Due to that, this project aims to get initial understanding about thermal storage system by design a mini thermal storage charging (during nighttime) and discharging (during daytime) for air-conditioning system. This report discusses about the background of this project regarding thermal storage operating strategy, system operation and design of mini thermal storage system. The project is based on the thermal storage system at Universiti Technologi PETRONAS's Gas District Cooling but simpler and smaller. An analysis also was conducted on storage tank to characterize the thermal storage tank.